Mental health and wellbeing of retired elite and amateur rugby players and non-contact athletes and associations with aports-related concussion: the UK Rugby Health Project - Hind, K.; Konerth, N.; Entwistle, I.; Hume, P.; Theadom, A.; Lewis, G.; King, D.; Goodbourn, T.; Bottiglieri, M.; Ferraces-Riegas, P.; Ellison, A.; Chazot, P. (Sports Medicine, 2022)
Background: Concerns have intensified over the health and wellbeing of rugby union and league players, and, in particular, about the longer-term effects of concussion. The purpose of this study was to investigate whether there were differences in mental health, sleep and alcohol use between retired elite and amateur rugby code players and non-contact athletes, and to explore associations with sports-related concussion. Methods: 189 retired elite (ER, n = 83) and amateur (AR, n = 106) rugby code players (rugby union n = 145; rugby league n = 44) and 65 former non-contact athletes (NC) were recruited to the UK Rugby Health Project between 2016 and 2018. Details on sports participation and concussion history were obtained by questionnaire, which also included questions on mental health, anger, sleep, mood, alcohol use, social connections and retirement from injury. Data were compared between sports groups (ER, AR and NC), between exposure of three or more or five or more concussions and for years in sport. Results: ER reported more concussions than AR (5.9 ± 6.3 vs. 3.7 ± 6.3, p = 0.022) and NC (0.4 ± 1.0, p < 0.001). ER had a higher overall negative mental health score (indicating poor mental health) than AR (10.4 ± 6.3 vs. 7.4 ± 6.5, d = 0.47, p = 0.003) and NC (7.1 ± 4.8, d = 0.57, p = 0.006) and a lower overall positive score (indicating good mental health) than NC (8.9 ± 4.1 vs. 10.7 ± 3.4, d = 0.46, p = 0.021). Negative scores were highest and positive scores lowest in those reporting three or more concussions (d = 0.36, p = 0.008; d = 0.28, p = 0.040, respectively) or five or more concussions (d = 0.56, p < 0.001; d = 0.325, p = 0.035, respectively). Reported symptoms for sleep disruption were more prevalent in ER than NC, and in former athletes with three or more concussions (d = 0.41-0.605, p < 0.05). There were no significant differences in alcohol score (p = 0.733). Global anger score and covert anger expression was higher in former athletes with five or more concussions (d = 0.32, p = 0.035; d = 0.37, p = 0.016). AR reported greater attachment to friends than NC (d = 0.46, p = 0.033) and 20% of ER reported that they would not turn to anyone if they had a problem or felt upset about anything. Conclusion: There was a significantly higher prevalence of adverse mental health and sleep disruption in ER and in former athletes who reported a higher number of concussions. Anger and irritability were more prevalent in former athletes with a history of five or more concussions. Strategies are needed to address mental health and sleep disturbance in elite rugby code athletes, who are also less likely to seek help should they need it. Further research is needed to elucidate causation, and the neurobiological connection between concussion, sub-concussions and longer-term psychological health and wellbeing.